Direct Catalytic Asymmetric Aldol Reaction of an α‐Azido Amide1. Issue 21 (30th March 2015) - Weidner, Karin; Sun, Zhongdong; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract A direct aldol reaction of an α‐azido 7‐azaindolinylamide, promoted by a Cu‐based cooperative catalyst, is documented. Aromatic aldehydes bearing an ortho substituent exhibited diastereodivergency depending on the nature of the chiral ligands used. Smooth reactions with ynals highlighted the broad substrate scope. A vicinal azido alcohol unit in the product allowed direct access to the corresponding aziridine and facile hydrolysis of the 7‐azaindolinylamide moiety furnished enantioenriched β‐hydroxy‐α‐azido carboxylic acid derivatives.